Contemporary Arab broadcast media - Lahlali, El Mustapha (Edinburgh Edinburgh University Press, 2011)
The Arab world is undergoing a media revolution, triggered by the launch of numerous, privately-owned satellite and cable TV channels. This book follows three dominant Arab media channels--Al-Jazeera, Al-Hurra, and Al-Arabia--as they have grown in importance and presence after the events of 9/11. It surveys the modern history of Arab media; the aims, objectives, and programs of Al-Jazeera Arabic, Al-Hurra, and Al-Arabia; and the similarities and differences between these channels' broadcasting. The volume explores the impact of private media on the Arabic public sphere, the American and European media's influence on Arab programming, the media laws under which Arab media operates, the issue of state control and ownership, and the extent of such influence on the dissemination of free and fair information.
1. Historical development of the Arab media -- 2. Globalization, democracy and the Arab media -- 3. Al-Jazeera, Al-Hurra and Al-Arabiya: Different Channels or three sides of the same triangle? -- 4. The Arab media and the discourse of conflict.
Electronic reproduction.
Keywords: Al Jazeera (Television network); Alhurra (Television network); Al-Arabia (Television network); Television broadcasting -- Arab countries; Electronic books